INTEGRASI METODE SWOT DAN QFD UNTUK MENINGKATAN DAYA SAING USAHA MELALUI PENGEMBANGAN PRODUK OTAK-OTAK BANDENG GRESIK - Narto Narto (Universitas Ahmad Dahlan Indonesia, 2020)
Gresik milkfish brain is a commodity from strategic ponds that has high economic value. An increase in population and high competition in the industrial era 4.0, the industry must be supported by competitive strategies to obtain a broad market share. To win the competition the industry must innovate products in accordance with consumer demand. The purpose of this research is to identify strengths and weaknesses as well as opportunities and threats, find out the desires and needs of consumers that have not been fulfilled in the preparation of milkfish brains, design effective business strategies through product development. Based on the results of the research using the SWOT method, a competitiveness strategy is obtained that is designing attractive packaging with the characteristics of the city of Gresik by using special materials that are environmentally friendly, product innovation oriented to new product variants, building a system of purchasing raw materials and supporting materials as well as integrated sales distribution, materials raw choice and processing of production processes that adopt technology. Product development that can be done with the QFD approach is to create new variants with priority on original, sweet, spicy flavors, each package uses an ergonomic design and secondary colors. The inner packaging material is coated with an antimicrobial edible coating